The influence of gamification, customer experience, and customer engagement on brand equity in Thai e-marketplace - Tangsophon, Suphicha; Udomratanamanee, Theerakorn; Siriudomset, Watcharit (Edelweiss Applied Science and Technology, 2025)
This study explores the impact of gamification, customer experience, and customer engagement on brand equity within Thai e-marketplaces, focusing on Shopee and Lazada, two of the largest online shopping platforms in Thailand. As gamification becomes increasingly integrated into digital commerce strategies, understanding its influence alongside experiential and behavioral variables is essential. Drawing from theories such as Self-Determination Theory, the Theory of Planned Behavior, and the Customer-Based Brand Equity model. The study employed a quantitative research design and surveyed 498 adult consumers in Bangkok who had recently used Shopee or Lazada. Multiple regression analysis revealed that customer experience and customer engagement significantly and positively influenced brand equity. However, gamification showed a non-significant negative relationship with brand equity, suggesting that gamified features alone may not enhance brand value in this context. The findings demonstrate the need for customer-centric strategies in digital retail environments. While gamification can increase interaction, its role may be more effective when aligned with broader experiential and engagement goals. The study offers practical implications for digital marketers and e-commerce platform managers, particularly in leveraging experience design and engagement tactics to strengthen brand equity.